Genotype-by-environment interaction effects on blast disease severity and genetic diversity of advanced blast-resistant rice lines based on quantitative traits - Salleh, Syafiqah Binti; Rafii, Mohd Yusop; Ismail, Mohd Razi; Ramli, Asfaliza; Chukwu, Samuel C.; Yusuff, Oladosu; Hasan, Nor’Aishah (Frontiers in Agronomy, 2022)
Among the rice diseases, rice blast caused by the pathogen Magnaporthe oryzae is a major threat to the global rice cultivation. This experiment was aimed at investigating the genotype by environment interaction effects on the severity of blast disease and genetic variation of the advanced blast resistant rice lines using quantitative characters. The experiment was laid out in randomized complete block design (RCBD) conducted at three locations. Data were collected on 21 traits which included vegetative, physiological, yield and yield components and were subjected to analysis of variance and variance component analysis. Cluster analysis was authenticated using principal component analysis for genotypes’ classification. All vegetative and yield traits showed highly significant variation among the advanced genotypes. Seberang Prai showed the highest average yield (5.62t/ha), followed by Tanjung Karang (5.39t/ha) and UPM (4.97t/ha). All the advanced genotypes showed high resistance to the blast disease. Evaluation across the three environments indicated that genotype G3, from MR219 based population, had the highest yield and resistance to blast infection. Genotype G21, from MR263 based population, performed best across the three environments studied. The totals of 11 clusters obtained were recommended as varieties for commercial cultivation in Malaysia and other rice growing regions.